An application of asymmetric GARCH models on volatility of banks equity in Nigeria's stock market - Omorogbe J. Asemota; Ucheoma C. Ekejiuba (CBN Journal of Applied Statistics, 2017)
This paper examines the volatility of banks equity weekly returns for six banks (coded B1 to B6) using GARCH models. Results reveal the presence of ARCH effect in B2 and B3 equity returns. In addition, the estimated models could not find evidence of leverage effect. On evaluating the estimated models using standard criteria, EGARCH (1, 1) and CGARCH (1, 1) model in Student's t-distribution are adjudged the best volatility models for B2 and B3 respectively. The study recommends that in modelling stock market volatility, variants of GARCH models and alternative error distribution should be considered for robustness of results. We also recommend for adequate regulatory effort by the CBN over commercial banks operations that will enhance efficiency of their stocks performance and reduce volatility aimed at boosting investors' confidence in the banking sector.
Keywords: C22; C52; C58; G12; G21; 330; Equity; Volatility; Stock Market Returns